Combined analysis of estradiol and β-hCG to predict the early pregnancy outcome of FET: a retrospective study - Man Wu; Xiao Xiao; Chen Wang; Min Zhao; Fang Xiong; Xin Jin; Xiaomin Zheng (BMC, 2024)
Abstract Background The accurate prediction of pregnancy outcomes in in vitro fertilization (IVF) cycles is crucial. While several studies have been conducted on the predictive power of serum estradiol (E2) and β-hCG concentrations post-embryo transfer (ET) for pregnancy outcomes, there is debate on the predictive value of E2. The objective of this study was to investigate the predictive efficacy of combining serum E2 and β-hCG levels on early reproductive outcomes 12 days after embryo transfer. Methods A total of 1521 patients with β-hCG positive values on day 12 following frozen-thawed embryo transfer (FET) with natural endometrial preparation cycles (NCs) were gathered in affiliated Women's Hospital of Jiangnan University. Using logistic regression, the relationship between pregnancy outcome and early serum E2 and β-hCG concentrations was examined. The receiver-operating characteristic (ROC) analysis was used to assess the predictive accuracy of the serum E2 and β-hCG concentrations. Results Notable distinctions were observed in the serum E2 and β-hCG levels on the twelfth day following FET with NCs between the groups classified as clinical pregnancy group (CP Group) and biochemical pregnancy group (BP Group). In addition, the cutoff values for E2 and β-hCG on day 12 following FET with NCs in cleavage embryo group (CE Group) were 129.25 pg/mL and 156.60 mIU/mL, respectively. The threshold values for E2 and β-hCG for the blastocyst group (B Group) were 174.45 pg/mL and 217.70 mIU/mL. Serum E2 day12 and β-hCG day12 were found to be substantially linked with clinical pregnancy by logistic regression analysis. Conclusions Serum E2 and β-hCG concentrations were found to be significantly different between the CP Group and BP Group in infertility women underwent FET with NCs. Our retrospective cohort study's findings suggest that the combination of early E2 and β-hCG levels on day 12 post-FET could be used as a predictive tool to evaluate the likelihood of both positive and negative pregnancy outcomes in FET with NCs.